Examining the Impact of User-Generated Content and Firm-Generated Content on Brand Equity: The Mediating Role of Brand Credibility in Private Higher Education - Meranga, Isana Sri Christina (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
The increasingly fierce competition in higher education, especially among private universities, has driven a focus on enhancing brand equity with the goal of establishing a unique position through sustainable branding strategies. This research aims to examine the role of social media communication as a crucial factor in building brand equity. This communication involves User-Generated Content and Firm-Generated Content through brand credibility. Data was collected through electronic questionnaires from 300 students across four private universities. The gathered data was analyzed using PLS-SEM. The research results indicate that User-Generated Content and Firm-Generated Content have a positive influence on brand credibility. This research demonstrates that brand credibility mediates the relationship between User-Generated Content and Firm-Generated Content and brand equity. The study contributes to the branding literature by revealing essential elements in building brand equity in the higher education sector that require further attention. Additionally, this research provides insights to universities about the significant role of User-Generated Content in shaping brand credibility, ultimately contributing to brand equity development.